Phorbol ester reduces ethanol excitation of dopaminergic neurons of the ventral tegmental area: involvement of protein kinase C theta - Nimitvilai, Sudarat; Arora, Devinder S.; You, Chang; McElvain, Maureen A.; Brodie, Mark S. (Frontiers in Integrative Neuroscience, 2013)
Neurons of the ventral tegmental area (VTA) play a key role in the rewarding and reinforcing effects of drugs of abuse, including alcohol. Ethanol directly increases the firing rate of dopaminergic (DAergic) VTA neurons, but modulation of the firing rate of DAergic VTA neurons can be controlled by a number of factors, including some that are under the control of protein kinase C (PKC). Application of phorbol esters activates PKC and the present study assessed the effect of a phorbol ester, phorbol 12-myristate 13-acetate (PMA), on ethanol-induced excitation of DA VTA neurons. Ethanol-induced excitation of DAergic VTA neurons was reduced significantly in the presence of PMA. This action of PMA was antagonized by chelerythrine chloride, a non-selective antagonist of PKC, but not by moderate concentrations of antagonists of conventional PKC isoforms (Gö6976 and Gö6983). A PKC δ/θ inhibitor antagonized PMA-induced reduction of ethanol excitation. Since PKCδ antagonist Gö6983 did not antagonize the effect of PMA on ethanol excitation, the PMA reduction of ethanol excitation is most likely to be mediated by PKCθ. Antagonists of intracellular calcium pathways were ineffective in antagonizing PMA action on ethanol excitation, consistent with the lack of calcium dependence of PKCθ. In summary, ethanol-induced excitation of VTA neurons is attenuated in the presence of PMA, and this attenuation appears to be mediated by PKCθ. This novel mechanism for interfering with ethanol activation of reward-related neurons could provide a new target for pharmacotherapy to ameliorate alcoholism.